Molecular Biology of Liver Cancer Stem Cells - Oishi, Naoki (S. Karger AG, 2014)
Hepatocellular carcinoma (HCC) is one of the most common and lethal cancers worldwide. The concept of cancer stem cells (CSCs) is based primarily on the clinical and experimental observations that indicate the existence of a subpopulation of cells with the capacity to self-renew and differentiate as well as show increased resistance to radiation and chemotherapy. They are considered as the factors responsible for the cases of tumor relapse. Hepatic progenitor cells (HPCs) could form the basis of some hepatocellular carcinomas (HCC) and cholangiocarcinomas. Liver CSCs have been reported in multiple subtypes of HCC and are considered as the master regulators of HCC initiation, tumor metastasis, and progression. HPCs activators such as epithelial cell adhesion molecule (EpCAM), Wnt/β-catenin, transforming growth factor-beta (TGF-β), Notch and Hedgehog signaling systems expedite tumorigenesis or conversely, serve as a powerful cancer-prevention tool. Recent work has also identified Sal-like protein 4 (SALL4) and some epigenetic regulations as important molecules, while several therapeutic drugs that directly control HPCs have been tested both in vivo and in vitro. However, liver CSCs clearly have a complex pathogenesis, with the potential for considerable crosstalk and redundancy in signaling pathways. Hence, the targeting of single molecules or pathways may have limited benefit for treatment. In addition to the direct control of liver CSCs, many other factors are needed for CSC maintenance including angiogenesis, vasculogenesis, invasion and migration, hypoxia, immune evasion, multiple drug resistance, and radioresistance. Here, we provide a brief review of molecular signaling in liver CSCs and present insights into new therapeutic strategies for their targeting.